Situational diagnosis on breast cancer training in the perception of health professionals (Research, Society and Development, 2022)
Breast cancer (BC) is the disease that kills most women worldwide, making it a serious public health problem. Due to its high incidence and mortality rate, it is one of the most preventable cancers and due to difficulties in accessing mammography in some regions, many cities do not reach the agreed goal for tumor screening. Therefore, this study aimed to make a diagnosis on the situation of breast cancer screening in the perception of health professionals. 4th Health Region of Alagoas, from March to September 2017. The professionals surveyed were mostly female, with 98.1% nurses and 66.7% doctors, Brazilians. More than 80% of respondents said they know the risk factors and all believe that mammography is important. In view of the results achieved, it was observed that the professionals of the teams of the family health units are aware of the importance of breast cancer screening, at the three levels of primary, secondary and tertiary prevention. The contractual goals will only be met when more effective measures are taken in the participation of municipalities to ensure breast cancer screening, both in access to mammography and complementary exams, which involves from raising women's awareness of the importance of self-care and carrying out the screening exams.